Cu(OH)2@CoCO3(OH)2·nH2O Core–Shell Heterostructure Nanowire Array: An Efficient 3D Anodic Catalyst for Oxygen Evolution and Methanol Electrooxidation. Issue 7 (7th December 2016) - Xie, Lisi; Tang, Chun; Wang, Kunyang; Du, Gu; Asiri, Abdullah M.; Sun, Xuping
Abstract : A Cu(OH)2 @CoCO3 (OH)2 · n H2 O (CCHH) core–shell heterostructure nanowire array acts as robust 3D oxygen evolution reaction catalyst. It needs an overpotential of 270 mV to drive 50 mA cm −2 in 1.0m KOH, outperforming CCHH nanowire arrays on copper foam and most reported Co‐based oxygen evolution reaction catalysts in alkaline media. It is also efficient for methanol electrooxidation.